International Consumption Risk Sharing and Monetary Policy - Sven Blank (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
This project aims at analyzing the impact of monetary policy on the international allocation of risk in a two-country dynamic stochastic general equilibrium model with sticky prices and international portfolio choice. The model features endogenous firms entry which influences the evolution of equity in each country and alters real exchange rate dynamics. Preliminary results show that there may be substantial deviations from efficient consumption risk sharing in the presence of monetary policy when there are frictions in goods as well as asset markets.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: F32; F42; E44; 330; International portfolio choice; consumption risk sharing; monetary policy; frictions